A genome-wide association study identifies Arabidopsis thaliana genes that contribute to differences in the outcome of infection with two Turnip mosaic potyvirus strains that differ in their evolutionary history and degree of host specialization. Issue 2 (30th June 2021) - Butković, Anamarija; González, Rubén; Rivarez, Mark Paul Selda; Elena, Santiago F
Abstract: Viruses lie in a continuum between generalism and specialism depending on their ability to infect more or less hosts. While generalists are able to successfully infect a wide variety of hosts, specialists are limited to one or a few. Even though generalists seem to gain an advantage due to their wide host range, they usually pay a pleiotropic fitness cost within each host. On the contrary, a specialist has maximal fitness within its own host. A relevant yet poorly explored question is whether viruses differ in the way they interact with their hosts' gene expression depending on their degree of specialization. Using a genome-wide association study approach, we have identified host genes whose expression depends on whether hosts were infected with more or less specialized viral strains. Four hundred fifty natural accessions of Arabidopsis thaliana were inoculated with Turnip mosaic potyvirus strains with different past evolutionary histories and that shown different degrees of specialization. Three disease-related traits were measured and associated with different sets of host genes for each strain. The genetic architectures of these traits differed among viral strains and, in the case of the more specialized virus, also varied along the duration of infection. While most of the mapped loci were strain specific, one shared locus was mapped for both strains, a disease-resistance TIR-NBS-LRR class protein. Likewise, only putative cysteine-rich receptor-like protein kinases were involved in all three traits. The impact on disease progress of 10 selected genes was validated by studying the infection phenotypes of loss-of-function mutant plants. Nine of these mutants have altered the disease progress and/or symptoms intensity between both strains. Compared to wild-type plants six had an effect on both viral strains, three had an effect only on the more specialized, and two were significant during infection with the less specialized.